2017
DOI: 10.5194/gmd-10-1403-2017
|View full text |Cite
|
Sign up to set email alerts
|

Global gridded crop model evaluation: benchmarking, skills, deficiencies and implications

Abstract: International audienc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
226
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 244 publications
(262 citation statements)
references
References 71 publications
15
226
0
1
Order By: Relevance
“…Nitrate movement with water fluxes is simulated as in SWAT (Neitsch et al, 2002(Neitsch et al, , 2005. Nitrate is assumed to be fully dissolved in water and moves with surface runoff, lateral runoff, and percolation water.…”
Section: Nitrogen Leaching and Movementmentioning
confidence: 99%
“…Nitrate movement with water fluxes is simulated as in SWAT (Neitsch et al, 2002(Neitsch et al, , 2005. Nitrate is assumed to be fully dissolved in water and moves with surface runoff, lateral runoff, and percolation water.…”
Section: Nitrogen Leaching and Movementmentioning
confidence: 99%
“…photosynthesis, respiration and evapotranspiration) and modules specifically designed to represent crop processes. The version of ORCHIDEE-CROP used in this study includes a crop phenology module (Wu et al, 2016) and crop management modules (Wang, 2016), and has also submitted results for global gridded crop model intercomparison (Müller et al, 2017). ORCHIDEE-CROP calculates thermal unit accumulation, photosynthesis and energy exchange on a half-hourly time step, while leaf area dynamics, carbon allocation, and biomass and soil organic carbon change are simulated on a daily time step.…”
Section: Orchidee-cropmentioning
confidence: 99%
“…The temporal variance of simulated crop yields is often not affected We also use the online tool as supplied by Müller et al (2017) for comparing the crop yield simulations against the Global Gridded Crop Model Intercomparison (GGCMI) model ensemble. Also here, results show that LPJmL 5 improves with respect to reproducing absolute yield levels across different countries, but that there is little effect on the simulated inter-annual 10 variability of crop yields.…”
Section: Crop Yieldsmentioning
confidence: 99%
“…Climate-carbon cycle feedbacks have become integral parts of Earth System Models (ESMs) for climate change projections. However, the terrestrial carbon cycle dynamic are not only driven by climate and carbon dioxide (CO 2 ) fertilization (Schimel et al, 2015;Norby et al, 2005), but also by land-use change (Müller et al, 2006(Müller et al, , 2016Arneth et al, 2017;Le Quéré et al, 2016) and vegetation dynamics (Müller et al, 2016, and references therein). Nutrient limitations, especially from nitro-15 gen, are also important constraints on vegetation growth and the terrestrial carbon cycle: Smith et al (2016) suggested that Earth System Models contributing to the CMIP5 data archive overestimate the response of net primary productivity to elevated CO 2 because the models largely miss the constraints from nutrient limitation.…”
mentioning
confidence: 99%